Household-specific barriers to citizen-led flood risk adaptation - Ben C. Howard; Cynthia A. Awuni; Samuel Agyei-Mensah; Lee D. Bryant; Alexandra M. Collins; Sandow Mark Yidana; Gerald A. B. Yiran; Wouter Buytaert (npj Climate Action)
Abstract Adaptation is essential to mitigate the effects of climate change, such as increasing flood risk. In response to widespread maladaptation, citizen-led approaches are increasingly championed, whereby people on the frontline of climate change determine their own objectives and strategies of adaptation. Enabling equitable and effective citizen-led adaptation requires an understanding of the barriers for different groups of people but this is currently lacking, especially in low- and middle-income countries. Using responses to a co-produced household survey (n = 286) in Tamale, Ghana, we show that barriers to citizen-led adaptation interventions (n = 11) differ between households which we relate to important components of adaptive capacity. Overall, awareness, education, and networks are the most important barriers, but resources and time are important for poor households of fewer members. Barriers also differ between interventions and overall structural interventions are preferred over behavioural. This work can inform policies and actions to support effective and equitable citizen-led adaptation.